An epithelial biomarker signature for idiopathic pulmonary fibrosis: an analysis from the multicentre PROFILE cohort study. Issue 12 (December 2017) - Maher, Toby M; Oballa, Eunice; Simpson, Juliet K; Porte, Joanne; Habgood, Anthony; Fahy, William A; Flynn, Aiden; Molyneaux, Philip L; Braybrooke, Rebecca; Divyateja, Hrushikesh; Parfrey, Helen; Rassl, Doris; et al.
Summary: Background: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal disorder with a variable disease trajectory. The aim of this study was to assess potential biomarkers to predict outcomes for people with IPF. Methods: PROFILE is a large prospective longitudinal cohort of treatment-naive patients with IPF. We adopted a two-stage discovery and validation design using patients from the PROFILE cohort. For the discovery analysis, we examined 106 patients and 50 age and sex matched healthy controls from Nottingham University Hospitals NHS Trust and the Royal Brompton Hospital. We did an unbiased, multiplex immunoassay assessment of 123 biomarkers. We further investigated promising novel markers by immunohistochemical assessment of IPF lung tissue. In the validation analysis, we examined samples from 206 people with IPF from among the remaining 212 patients recruited to PROFILE Central England. We used the samples to attempt to replicate the biomarkers identified from the discovery analysis by use of independent immunoassays for each biomarker. We investigated the predictive power of the selected biomarkers to identify individuals with IPF who were at risk of progression or death. The PROFILE studies are registered onClinicalTrials.gov, numbersNCT01134822 (PROFILE Central England) andNCT01110694 (PROFILE Royal Brompton Hospital). Findings: In the discovery analysis, we identified four serum biomarkers (surfactant protein D, matrix metalloproteinase 7, CA19-9, and CA-125) that were suitable for replication. Histological assessment of CA19-9 and CA-125 suggested that these proteins were markers of epithelial damage. Replication analysis showed that baseline values of surfactant protein D (46·6 ng/mL vs 34·6 ng/mL, p=0·0018) and CA19-9 (53·7 U/mL vs 22·2 U/mL; p<0·0001) were significantly higher in patients with progressive disease than in patients with stable disease, and rising concentrations of CA-125 over 3 months were associated with increased risk of mortality (HR 2·542, 95% CI 1·493–4·328, p=0·00059). Interpretation: We have identified serum proteins secreted from metaplastic epithelium that can be used to predict disease progression and death in IPF. Funding: GlaxoSmithKline R&D and the UK Medical Research Council.